Advances in Environmental Engineering - Adriana Estokova (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The book presents research papers addressing a wide range of environmental topics: water and wastewater treatment and management, soil degradation and conservation, sediment pollution control, environmental impacts of technologies, life cycle analysis (LCA), air quality and indoor environment, and advanced environmental materials. The contributions provide novel and significant scientific results and advanced applications in the field of environmental engineering and provide an integrated view of the trends in solving the problems associated with the achievement of sustainability.